VALUE CO CREATION STUDY ON VENDOR BUSINESS MODEL - Sholehuddin, Sulton; Sudarmiatin; Hermawan, Agus (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
Researchers will further examine the process of creating co-creation in SMEs businesses with an analysis of strength, opportunity, aspiration, and results (SOAR). How a shared value creation strategy plays a role in the development of an entrepreneur's business strategy. SOAR analysis enables members of an organization to create their own desired future in the entire process by means of inquiry, imagination, innovation, and inspiration. SOAR's internal focus is organizational strength. This research will examine the business strategy of entertainment vendor service entrepreneurs, namely Backstage Production in this case event equipment service providers. As a result, Backstage Production has applied the SOAR concept very well to create corporate image and value. Although some things can be maximized again, each model makes a positive contribution and is believed to be able to contribute sustainably in strengthening the company, especially in the current era of society 5.0